Transferred children and the production of family violence in French Polynesia: social change and the adaptations of fa'a'amura'a - Bastide, Loïs (Family violence and social change in the Pacific Islands, 2023)
In this chapter, we focus on the relationship between mobilities within the family - particularly frequent in French Polynesia, where individuals typically move many times between different households during their life course - and violence within the family. To explore this relationship, we highlight the specific situation of children who are raised, cared for, or fostered by adults other than their biological parents (fa’a’amu children). We show that the transfer of children and parental authority - a common social practice in the region - lay the groundwork for the development of heightened forms of vulnerability with regards to family violence.